Qardh al-Hasan as a Tool for Urban Justice: A Comparative Fiqh Perspective for Financial Inclusion in Bandung’s MSME Sector - Ahmad Ridwansah, Asep; Susandi, Adi; Jubaedah , Dedah; Setiawan, Iwan; Sudrajat, Dede (Zona Law And Public Administration Indonesia, 2025)
Abstract This conceptual study employs a comparative fiqh (Islamic jurisprudence) perspective to analyze Qardh al-Hasan (benevolent, interest-free loans) as an instrument for urban financial inclusion in Bandung, Indonesia. Through a systematic literature review enhanced with jurisprudential analysis, the research examines divergent interpretations across Islamic legal schools (madhahib) and their implications for implementing Qardh al-Hasan within Bandung's MSME sector. The study aims to: (1) analyze comparative fiqh debates on Qardh al-Hasan as a developmental tool, (2) identify operational variations in different Muslim-majority urban contexts, and (3) formulate an inclusive governance model synthesizing juristic flexibility with contemporary urban needs. Findings reveal that while classical fiqh emphasizes Qardh al-Hasan's charitable nature, contemporary juristic innovations (takyīr fiqhi) permit structural adaptations that enhance sustainability without compromising Sharia principles. The proposed Tripartite Partnership Model integrates comparative fiqh insights with urban governance theory, offering a flexible framework adaptable to Bandung's socio-economic landscape while maintaining juristic integrity. This research contributes to the discourse on Islamic financial inclusion by demonstrating how juristic pluralism can inform practical policy solutions for urban poverty alleviation.